Application of density functional theory for evaluating the mechanical properties and structural stability of dental implant materials - Ravinder Singh Saini; Seyed Ali Mosaddad; Artak Heboyan (BMC, 2023)
Abstract Background Titanium is a commonly used material for dental implants owing to its excellent biocompatibility, strength-to-weight ratio, corrosion resistance, lightweight nature, hypoallergenic properties, and ability to promote tissue adhesion. However, alternative materials, such as titanium alloys (Ti-Al-2 V) and zirconia, are available for dental implant applications. This study discusses the application of Density Functional Theory (DFT) in evaluating dental implant materials' mechanical properties and structural stability, with a specific focus on titanium (Ti) metal. It also discusses the electronic band structures, dynamic stability, and surface properties. Furthermore, it presents the mechanical properties of Ti metal, Ti-Al-2 V alloy, and zirconia, including the stiffness matrices, average properties, and elastic moduli. This research comprehensively studies Ti metal's mechanical properties, structural stability, and surface properties for dental implants. Methods We used computational techniques, such as the CASTEP code based on DFT, GGA within the PBE scheme for evaluating electronic exchange-correlation energy, and the BFGS minimization scheme for geometry optimization. The results provide insights into the structural properties of Ti, Ti-Al-2 V, and zirconia, including their crystal structures, space groups, and atomic positions. Elastic properties, Fermi surface analysis, and phonon studies were conducted to evaluate the tensile strength, yield strength, ductility, elastic modulus, Poisson's ratio, hardness, fatigue resistance, and corrosion resistance. Results The findings were compared with those of Ti-Al-2 V and zirconia to assess the advantages and limitations of each material for dental implant applications. This study demonstrates the application of DFT in evaluating dental implant materials, focusing on titanium, and provides valuable insights into their mechanical properties, structural stability, and surface characteristics. Conclusions The findings of this study contribute to the understanding of dental implant material behavior and aid in the design of improved materials with long-term biocompatibility and stability in the oral environment.